Overexpression of Rosea1 From Snapdragon Enhances Anthocyanin Accumulation and Abiotic Stress Tolerance in Transgenic Tobacco - Naing, Aung H.; Ai, Trinh N.; Lim, Ki B.; Lee, In J.; Kim, Chang K. (Frontiers in Plant Science, 2018)
Co-expression of Rosea1 (Ros1) and Delila (Del) controls regulation of anthocyanin in snapdragon flowers, whereas their overexpression in tomatoes, petunias, and tobacco also exhibited similar functions. However, little data exist on how Ros1 expression alone controls anthocyanin regulation and whether it is involved in the mechanism that leads to abiotic stress tolerance. Overexpression of Ros1 promoted accumulation of anthocyanin in leaves and flowers of tobacco (Nicotiana tabacum ‘Xanthi’) by elevating all key biosynthesis genes; promotion largely occurred through regulation of NtDFR and NtANS in the former and elevation of NtDFR transcript levels in the latter. Under normal conditions, T2-Ros1 and the wild type (WT) were able to survive by producing well-developed broad leaves and regular roots, whereas a reduction in plant growth was observed under cold and drought stress. However, the T2-Ros1 was able to tolerate the stresses better than the WT by induction of greater reactive oxygen species (ROS) scavenging activity (DPPH, ABTS), antioxidant-related gene expression (SOD, CAT, and POX), and stress-responsive gene expression (CBF1, Osmotin, and ABA). In addition, Ros1 was phylogenetically clustered with other MYB TFs that confer different abiotic stresses. These results suggest that overexpression of Ros1 elevates the expression of the anthocyanin biosynthetic gene, antioxidant-related genes, and stress-responsive genes. The resultant increase in gene expression improves anthocyanin accumulation and abiotic stress tolerance.